The effect of brand image, product quality, price, and brand ambassador on purchase decisions of Scarlett Whitening in Pekalongan - Umiatun; Choliq Sabana; Dian Milasari; Mella Mardayanti (Business, Accounting, and Knowledge Journal, 2024)
This study aims to analyze the effect of brand image, product quality, price, and brand ambassadors on purchasing decisions for Scarlett Whitening consumers in Pekalongan City, Central Java, Indonesia. The research methods used in this study use quantitative methods. The population in this study were all people in Pekalongan City who had bought and become consumers of Scarlett Whitening products. The sample in this study was 100 respondents using the purposive sampling technique. The data analysis technique in this study is multiple linear regression analysis. The results of this study indicate that brand image has a positive and insignificant effect on purchasing decisions, product quality has a significant positive effect on purchasing decisions, price has a significant positive effect on purchasing decisions, and brand ambassadors have a significant positive effect on purchasing decisions.